2022
DOI: 10.3390/ijerph19159555
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Commonly Used Quality of Life Outcome Measures for Youth Self-Report

Abstract: Self-report measures are central in capturing young people’s perspectives on mental health concerns and treatment outcomes. For children and adolescents to complete such measures meaningfully and independently, the reading difficulty must match their reading ability. Prior research suggests a frequent mismatch for mental health symptom measures. Similar analyses are lacking for measures of Quality of Life (QoL). We analysed the readability of 13 commonly used QoL self-report measures for children and adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…This is in line with the findings of Kalfoss (2019), who identified that language issues often are relate to the ambiguity about the meaning of a word or where phrasing is idiomatic. When designing or translating a questionnaire it is important to identify unfamiliar words and replace these words or expressions with more family ones (Krause et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of Kalfoss (2019), who identified that language issues often are relate to the ambiguity about the meaning of a word or where phrasing is idiomatic. When designing or translating a questionnaire it is important to identify unfamiliar words and replace these words or expressions with more family ones (Krause et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research has identi ed that some measures have higher readability ages than the stated age range [44,45]. Co-developing a common measurement framework, with young person approved and age-appropriate measures, will allow for the better monitoring of SP and can help increase usage from those tasked with administration.…”
Section: Discussionmentioning
confidence: 99%
“…While it is important that there are robust measures for all aspects of mental wellbeing, common mental health problems and severe mental illness, the lack of consistency in the measures used means that important opportunities to compare findings across studies, settings and time are being missed. Additionally, the increase in the numbers of measures available has also led to concerns about the quality of measures that are used and the absence of independent evaluation of their psychometric properties (Addington et al, 2015 ; Howe et al, 2020 ), as well as if measures accurately reflect the different mental health outcome domains claimed (Krause et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%